Halal Certification as a Development Strategy: Insights from Dapur Reuni for Micro-Enterprise Competitiveness - Tri Utami Salsabila; Zuhrinal M Nawawi; Waizul Qarni (Research Synergy Foundation, 2025)
In response to growing consumer awareness of halal products and increasingly competitive markets, halal certification has emerged as a vital strategy for micro, small, and medium enterprises (MSMEs) to enhance competitiveness and expand market access, particularly in countries with a predominantly Muslim population, such as Indonesia. This study aims to explore in-depth how the implementation of halal certification contributes to the development of micro businesses by focusing on a case study of Dapur Reunion, an MSME operating in Medan City, Indonesia. Employing a qualitative approach and case study strategy, this research investigates processes, strategies, and impacts of halal certification through in-depth interviews, participatory observation, and document analysis involving business actors and their operational environments. The interviews were conducted with five respondents, including Dapur Reuni business actors and loyal consumers who consistently purchase products from Dapur Reuni MSMEs in Medan City. The findings reveal that halal certification plays a significant role in building consumer trust, strengthening brand image, widening market reach, and promoting innovation and operational efficiency. Additionally, the certification process encourages business owners to implement more structured production standards and maintain sustainability through consistent internal monitoring. The primary contribution of this study lies in providing empirical evidence on post-certification strategic dynamics from the perspective of MSME actors, which remains underexplored in existing literature. These findings are expected to serve as a practical reference for other MSMEs and inform policymakers and support institutions in developing a more inclusive and sustainable halal certification ecosystem.